Strategi Pengembangan Usaha Melalui Diversifikasi Produk dan Store Atmosphere Dalam Meningkatkan Volume Penjualan Coffee Shop Renjana - Basit, Abdul; Bahri Dg. Parani, Syamsul; Zahara, Zakiyah; Zeylo Auriza, Mohammad (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze business development strategies through product diversification and store atmosphere in increasing the sales volume of Renjana coffee shops. The methods used are mixed methods through interviews, observations, documentation, word clouds, and mean value analysis of 60 respondents. The results show that product diversification and store atmosphere received excellent ratings, supported by the dominance of positive words in the word cloud. Sales data increased from a stagnant range of 46%-54% to 70%-97% after the strategy was implemented. These findings confirm that both strategies are effective in creating a positive consumption experience and increasing Renjana's sales volume.